Educational Human Resource Management Strategies in the Digital Era - Apriyanto, Sigit; Anum, Adelina; Farhan, Raed Nafea (CV. Tripe Konsultan, 2025)
Digital transformation drove significant changes in various aspects of educational governance, including in the management of human resources (HR). This study aimed to identify and synthesise HR management strategies that had been implemented globally in response to the challenges and opportunities of digitalisation over the past decade. Employing a systematic review approach to 65 scholarly articles published between 2014 and 2024, this study mapped out best practices across six key areas: digital recruitment, professional training and development, technology-based performance evaluation, utilisation of digital platforms, workforce well-being, as well as policy and transformational leadership. The synthesis results revealed that the successful implementation of these strategies heavily depended on the social context, national policies, and the level of technological infrastructure readiness in each country. Educational institutions that were able to integrate technology with data-driven approaches, apply adaptive leadership, and prioritise holistic HR well-being proved to be more resilient and adaptable in facing digital disruption. Moreover, training programmes that combined the strengthening of technical skills with motivational support yielded more sustainable outcomes. This study also emphasised the importance of a systemic approach and cross-sector collaboration in designing HR policies that were responsive to digital developments. The findings were expected to serve as a reference for stakeholders in formulating educational policies that were more adaptive, inclusive, and focused on strengthening human capacity in the era of digital transformation.